Comparing efficacy of oral clonidine and gabapentin premedication for post-operative pain and analgesic requirement in patient undergoing laparoscopic cholecystectomy: A prospective, double-blind, and placebo-controlled study - Ravi Prakash; Amey Dixit; Kuldeep Kumar Patel; Ashish Malik (Asian Journal of Medical Sciences, 2022)
Background: Post-operative pain is an area, which has been receiving an increasing amount of attention in recent years. Pain associated with laparoscopic cholecystectomy has been an area of interest for many, various modalities have been tried for pain relief.